OPTIMALISASI APLIKASI RUANGGURU SEBAGAI SARANA PENUNJANG PEMBELAJARAN MATERI SINTAKSIS BAGI SISWA - Aditya Hendrawan (p-ISSN 2356-0576, 2020)
Abstract: The Covid-19 pandemic is a topic of discussion that is being widely discussed in the public. Many sectors affected by this pandemic as well as the economic sector, the industrial sector, the tourism sector, and also the education sector. The central government orders the adoption of large-scale social restrictions. Which resulted in all activities involving many individuals carried out in their respective homes. So that it also has an impact on the world of education and the learning process is carried out at home through online media. One of the supporting facilities for student learning is through the Ruangguru application. In the application there is also learning related to syntactic material. But in terms of optimizing the application related to sitaksis learning is still considered lacking by some people, especially people with lower middle income. This is because this application can be accessed as a whole if you have a subscription. Actually the solution to solve the problem is by making people aware that education is also an important provision in lifeKeywords: optimization, application, ruangguru.